Hybrid Cryptosystem Analysis RSA Algorithm And Triple DES Algorithm - Liana, Liana; Zarlis, Muhammad; Tulus, Tulus (Politeknik Ganesha Medan, 2023)
Data security is needed in terms of communication. To guarantee data security, a technique is needed to make data and information called Critography. This study aims to analyze the process of Super Encryption in symmetric and asymmetric criterias using the Triple DES Algorithm and the RSA Algorithm. This can improve data security so that data is more confidential. The method used in Triple DES which is also called the symmetric algorithm is the OFB (Output feeback) method, and the RSA Algorithm (Riverst - Shamir-Adleman) which is an asymmetric algorithm using a random number system so that when these two algorithms are combined in the Super Encryption process the more accurate the data security. Super DES Triple Encryption and RSA algorithm analysis shows that the data created by text will be encrypted into ciphertext using both methods and re-described, so that the security of the data is relatively safe. Super Encryption on the two methods Algorithm is done because the level of complexity is difficult to make Cryptanalysts to steal data and the Encryption process becomes slow but data security becomes safer and not easy to attack Cryptanalysts. The problem in this research is how to increase encryption security and speed up the encryption process by combining the RSA and Triple DES methods.